2006
DOI: 10.1007/s10533-005-4427-5
|View full text |Cite
|
Sign up to set email alerts
|

Tannin Dynamics of Propagules and Leaves of Kandelia candel and Bruguiera gymnorrhiza in the Jiulong River Estuary, Fujian, China

Abstract: Changes in the total phenolics, condensed tannins (CT), protein-precipitable phenolics content and protein precipitation capacity were determined on a series of mangrove leaves from two true viviparous mangrove species (Kandelia candel and Bruguiera gymnorrhiza) at various stages of development and decomposition in the Jiulong River Estuary, Fujian, China. Similar measurements were also done for the propagules at different developmental stages. The results showed that the total phenolics, extractable condensed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 36 publications
2
59
0
Order By: Relevance
“…Relationship between total phenolics and N contents during leaf decomposition of Bruguiera gymnorrhiza (Bg) and Kandelia candel (Kc). Symbols are: black triangle for Bg leaf; white triangle for Kc leaf (Adapted from Lin et al 2006). lated mass loss (Berg et al 1984).…”
Section: Roles Of Quantitative Chemical Traits On Leaf Litter Decompomentioning
confidence: 99%
“…Relationship between total phenolics and N contents during leaf decomposition of Bruguiera gymnorrhiza (Bg) and Kandelia candel (Kc). Symbols are: black triangle for Bg leaf; white triangle for Kc leaf (Adapted from Lin et al 2006). lated mass loss (Berg et al 1984).…”
Section: Roles Of Quantitative Chemical Traits On Leaf Litter Decompomentioning
confidence: 99%
“…Procedures described by Lin et al (2006) were used to determine total phenolics (TP), extractable condensed tannins (ECT). TP were measured with the Prussian blue method (Graham 1992), and ECT were assayed by the butanol-HCl method (Terrill et al 1992), using purified tannins from C. equisetifolia branchlets as the standard.…”
Section: Chemical Analysesmentioning
confidence: 99%
“…Procedures described by Lin et al (2006) were used to determine total phenolics (TP), extractable condensed tannins (ECT), protein bound condensed tannins (PBCT), and fibre bound condensed tannins (FBCT) and protein precipitation capacity (PPC) in the branchlet litter. TP concentrations were measured by the Foline Ciocalteu method (Zhou et al 2010), ECT, PBCT and FBCT were assayed by the butanol-HCl method (Terrill et al 1992), using purified tannins from C. equisetifolia branchlets as the standard.…”
Section: Methodsmentioning
confidence: 99%
“…Phenolic compounds, including tannins, are a significant component of plant secondary metabolites (Míka et al 2005, Lin et al 2006, Lachman et al 2011. Because high tannin concentrations in plants are often associated with infertile site conditions (Northup et al 1995), it has been suggested that there is an evolutionary advantage to higher tannin production.…”
Section: Changes Of Tannin and Nutrients During Decomposition Of Branmentioning
confidence: 99%
See 1 more Smart Citation